Clinical effect of sodium hyaluronate and cyclosporine A eye drops for combination treatment of mixed dry eye syndrome - Hai-Jing Shen (Guoji Yanke Zazhi, 2020)
AIM: To analyze the efficacy of sodium hyaluronate and cyclosporine A eye drops in treating patients with mixed dry eye disease. METHODS: Among patients diagnosed with dry eye who presented to our hospital between February 2018 to February 2019, 60(120 eyes)cases were divided into 30(60 eyes)in each control and treatment group by random number table method. Both groups received routine treatment with the methods of eyelid hot compress cleaning and meibomian gland massage. The treatment group received combined application of sodium hyaluronate eye drop(0.3%)and cyclosporine A eye drop(1%), while control group received carbomer eye drops used alone at four times daily. And dry eye symptom score, Schirmer I test(SⅠt), tear film break-up time(BUT)and corneal fluorescein staining(CFS)results were obtained before treatment, at the 1 and 3mo after initiation of treatment. RESULTS: No statistically differences were observed in any of the indexes between the control group(dry eye symptom score: 13.52±2.15, SⅠt: 5.22±2.23, BUT: 5.02±1.58, CFS:2.82±0.81)and the treatment group(dry eye symptom score: 13.75+3.05, SⅠt: 5.54+2.89, BUT: 5.14+1.84, CFS: 2.73±0.45)before initiating treatment. One month later, the dry eye symptom score of the control group(12.22±2.64)and the treatment group(11.42±2.06)improved after treatment; the SⅠt of the control group(7.94±2.15)and the treatment group(8.63±2.78)also improved after treatment, and result of the treatment group was better than that of the control group, and the difference was statistically significant; the BUT of the control group(5.32±1.34)and the treatment group(5.46±1.45)were better after treatment, but the difference was not statistically significant. After 3mo treatment, the dry eye symptom score, SⅠt, BUT and CFS of the control group were 11.57±2.98, 8.44±2.35, 5.92±1.75, 1.92±0.44, respectively, and the dry eye symptom score, SⅠt, BUT and CFS of the control group were 9.23±2.34, 10.45±2.65, 5.92±1.75, 8.69±1.78, 1.59±0.79, respectively(P<0.05). CONCLUSIONS: Combination therapy of sodium hyaluronate eye drop and cyclosporine A eye drops treatments are effective for the treatment of mixed dry eye syndrome.